Insertion/deletion polymorphism in the angiotensin-converting enzyme gene in myocardial infarction survivors - Hubacek, J A; Pitha, J; Podrapská, I; Sochman, J; Adámková, V; Lánská, V; Poledne, R (Medical science monitor, 2000)
INTRODUCTION: Insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE) gene influenced the plasma concentration of the ACE, and is D allele have been repetitively suggested as a risk factor for myocardial infarction (MI). MATERIAL AND METHODS: Two hundert thirty six male myocardial infarction survivors under 65 years and with body mass index and total plasma cholesterol levels under 95% of the Czech population were included in the study. As control group, 302 male controls (1% randomly selected group from the Czech population) were genotyped. I/D polymorphism in the ACE gene was determined using polymerase chain reaction. RESULTS: The prevalence of the I/I, I/D and D/D genotypes was 0.218, 0.494 and 0.288, in the control group, and 0.178, 0.538 and 0.284, in the myocardial survivors, respectively. The male Czech population has the similar frequency of insertion and deletion alleles compared to other Caucasian populations. The frequencies of the alleles and genotypes of the ACE gene did not differ significantly between MI survivors and a control sample of the Czech population. CONCLUSION: It was shown that the I/D polymorphism in the gene for ACE is not a genetic risk factor for myocardial infarction in the Czech population.
Keywords: přežívající; Male; Peptidyl-Dipeptidase A; Cholesterol, LDL; HDL-cholesterol; Genotype; polymorfismus genetický; LDL-cholesterol; Cholesterol, HDL; Česká republika; Cholesterol; Adult; transpozibilní elementy DNA; dospělí; mužské pohlaví; Survivors; angiotensin konvertující enzym; referenční hodnoty; Gene Deletion; triglyceridy; Polymorphism, Genetic; infarkt myokardu; Czech Republic; cholesterol; Reference Values; DNA Transposable Elements; lidé; krevní tlak; Humans; Body Mass Index; Myocardial Infarction; Blood Pressure; delece genu; Triglycerides; index tělesné hmotnosti; genotyp; lidé středního věku; Middle Aged